Cost-savings to medicare from pre-medicare colorectal cancer screening - Goede, S.; Kuntz, K.; Van Ballegooijen, M.; Knudsen, A.; Lansdorp_Vogelaar, Iris; Tangka, F.; Howard, D.; Chin, J.; Zauber, A.; Seeff, L. (2015)
Background: Many individuals have not received recommended colorectal cancer (CRC) screening before they become Medicare eligible at the age of 65. We aimed to estimate the long-term implications of increased CRC screening in the pre-Medicare population (50-64 y) on costs in the pre-Medicare and Medicare populations (65+ y). Methods: We used 2 independently developed microsimulation models [Microsimulation Screening Analysis Colon (MISCAN) and Simulation Model of CRC (SimCRC)] to project CRC screening and treatment costs under 2 scenarios, starting in 2010: "current trends" (60% of the population up-to-date with screening recommendations) and "enhanced participation" (70% up-to-date). The population was scaled to the projected US population for each year between 2010 and 2060. Costs per year were derived by age group (50-64 and 65+ y). Results: By 2060, the discounted cumulative total costs in the pre-Medicare population were $35.7 and $28.1 billion higher with enhanced screening participation, than in the current trends scenario ($252.1 billion with MISCAN and $239.5 billion with SimCRC, respectively). Because of CRC treatment savings with enhanced participation, cumulative costs in the Medicare population were $18.3 and $32.7 billion lower (current trends: $423.5 billion with MISCAN and $372.8 billion with SimCRC). Over the 50-year time horizon an estimated 60% (MISCAN) and 89% (SimCRC) of the increased screening costs could be offset by savings in Medicare CRC treatment costs. Conclusion: Increased CRC screening participation in the pre-Medicare population could reduce CRC incidence and mortality, whereas the additional screening costs can be largely offset by long-term Medicare treatment savings.